Characteristics of the Matuyama‐Brunhes Magnetic Field Reversal Based on a Global Data Compilation - Mahgoub, Ahmed Nasser; Korte, Monika; Panovska, Sanja; 1 Helmholtz Centre Potsdam, Deutsches GeoForschungsZentrum GFZ Section 2.3 – Geomagnetism Potsdam Germany (Journal of Geophysical Research: Solid Earth, 2023)
Magnetic field reversals are irregular events in Earth's history when the geomagnetic field changes its polarity. Reversals are recorded by spot and continuous remanent magnetization data collected from lava flows and marine sediments, respectively. The latest field reversal, the Matuyama‐Brunhes reversal (MBR), is better covered by paleomagnetic data than prior field reversals, hence providing an opportunity to understand the physical mechanisms. Despite the quantity of data, a full understanding of the MBR is still lacking. The evolution of the MBR in time and space is explored in this work by compiling a global set of paleomagnetic data, both from sediments and volcanic rocks, which encompass the period 900–700 ka. After careful evaluation of data and dating quality, regional and global stacks of virtual axial dipole moment (VADM), virtual geomagnetic pole (VGP), and paleosecular variation index (Pi) are constructed from the sediment records using bootstrap resampling. Individual VADMs and VGPs calculated from lavas are compared to these stacks. Four phases of full‐vector field instability are observed in these stacks over the period 800–770 ka. The first three phases, observed at 800–785 ka, reflect a rapid weakening of the field coupled with low VGP latitude, after which the field returned to the reverse polarity of the Matuyama chron. The fourth phase, lasting from 780 to 770 ka, is when the field reversal process completed, such that the field entered the Brunhes normal polarity state. These findings point to a complex reversal process lasting ∼30 Kyr, with the reversal ending at ∼770 ka. Plain Language Summary: The Earth's magnetic field, or geomagnetic field, which humans and some animals use for navigation, shields us from solar and cosmic radiation. The magnetic North and South poles have repeatedly, but infrequently changed their positions over Earth's history, a phenomenon known as magnetic field reversal. During a reversal, the magnetic field intensity decreased to low levels, which could have ...